Deteksi Coxiella burnetii Penyebab Q fever pada Sapi, Domba dan Kambing di Bogor dan Bali (DETECTION OF COXELLA BURNETII, THE CAUSAL AGENT OF Q FEVER - Mahatmi, Hapsari; Setiyono, Agus; Damayanti Soejoedono, Retno; Hasmi Pasaribu, Fachriyan (Jurnal Veteriner; Vol 8 No 4 (2007), 2007)
A study to detect Coxiella burnetii, an intracellular bacterium causing Q fever in human and livestock animals, was carried out in several ruminants in Bogor and Bali. The methods used for the detection was Nested-Polymerase Chain Reaction (Nested-PCR). Two pairs of primers, the first (OMP1 and OMP2) and the second (OMP3 and OMP4) were used to detect the genomic sequences and the conserved specific sequences of Coxiella burnetii, respectively. Organ samples such as liver and lung from 410 livestock ruminants, consisting of cattle (245 samples), sheep (105 samples) and goats (60 samples) were collected from several slaughter houses in Bogor and Bali. As many as 15 (6.12%) out of 245 cattle, 6 (5.71%) out of 105 sheep and none from goat were infected by Coxiella burnetii. Interestingly, 3 out of 15 infected cattle were Bali cattle. The results clearly indicate that Q fever is likely to be widespread among ruminant animals in Indonesia.
Keywords: Q fever, Coxiella burnetii, ruminant. nested-PCR